Pemberdayaan UPR Dian Farm untuk Kemandirian Pakan Alami dari Limbah Kotoran Sapi - Juliwati Putri Batubara; Pramudia Sinaga; Muhammad Lucky; Rafly Syahreva; Shella Wahyuni (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The problem with UPR Dian Farm is that water fleas are not available independently, causing a low survival rate of gouramy seeds (30–40%). Cow dung contains nutrients N and P, which can promote the growth of phytoplankton and bacteria, both of which serve as food sources for water fleas. Cow dung waste around the target partner location has not been optimally utilized as a medium for growing water fleas. The purpose of the service activity is to ensure that the target partners are able to produce water fleas independently, increasing the growth and survival of the carp seeds that are kept. The service method is in the form of lectures and discussions, as well as training. The results of service activities are able to increase the knowledge and skills of the target partners. The results of the test on cow dung that was fermented for 7 days showed the elemental content of C-organic = 13.31%, total N = 0.46%, P = 0.77%, and K = 0.30%. The results of the proximate analysis of water fleas obtained a protein content of 4.90%, fat of 42.10%, fiber of 4.85%, water of 96.64%, and ash of 2.22%. Water fleas given to gouramy seeds increased the absolute length of the seeds by 3.6 cm, with a relative growth rate of 0.12%/day. The absolute weight growth of gouramy seeds was 1.38 grams, with a relative weight growth rate of 0.046 %/day. The survival rate of gouramy seeds increased by up to 77%.